A biodigestão como ferramenta para a sustentabilidade avícola - Dornelas, Karoline Carvalho (2016)
The poultry industry is well developed and important activity for Brazil. However, it is a waste producing activity, especially solids, such as broiler litter. As an alternative to reduce the environmental impact and production costs of the activity, many poultry farmers employ the reuse of poultry litter for several consecutive batches. However, this reuse increases the concentration of micro-organisms, which can cause problems regarding health aspects. In this sense it is essential to adopt a pre-treatment of poultry litter during the fallow period between batches to avoid problems the birds of the subsequent batch. Among the procedures applied stands fermentation. It is known that the reuse of the bed occurs only a few lots, it follows that it is necessary sometime make the disposal of poultry litter. One of the possible ways to treatment (reduction of the risk of pollution) is the digestion process. Thus, the aim of the execution of this work was to evaluate if there is interference pretreatment fermentation of poultry litter in the digestion proce ss and evaluate the biogas potential and front power generation to different bed reuses numbers chickens. The work was to use poultry litter, rice husk, from two poultry houses, built on a small scale, where they were housed 60 birds per batch in a 14 birds density m2. The bed of the aviary 1 did not receive pre-treatment and the bed of the aviary 2 underwent pre-treatment (fermentation) in each batch of chicken production, the total were seven lots of chickens creations. Each batch removed, digestion process with a bed portion were performed with hydraulic retention time of 35 days. The results showed that in all tests was the production of biogas, and the quantized volumes ranged from 8.9 to 41.1 L of avian biogas to 1 and 6.7 to 33.9 L of biogas for avian 2, the largest biogas potential registered with reuse 6th bed in both aviaries. The slight difference in biogas production of avian 1 and 2 suggests that the pretreatment is stabilized by fermentation of the organic material which would be sent to the digestion process, reducing the total volume of biogas produced. average potential biogas, m3 kg-1 of total solids added were 0.022 to 0.034 for avian 1 (without pre- treatment fermentation bed during the fallowing) and 0.015 to 0.022 for avian 2 (fermentation bed). The energy values of the produced biogas calculated based on the calorific value ranged from 0.06 to 0.33 kWh for avian 1 and 0.05 to 0.27 kWh for avian 2. The results demonstrate the potential of poultry manure for biogas production and show that the fermentation in poultry litter prior to digestion process tends to reduce the volume of production of biofuel. Thus, through the digestion of poultry litter, the producer can generate power at low cost, realize the management right of the farm waste form, and environmentally collaborate, reducing the possible environmental impacts produced in the poultry activity, in addition to making the activity a sustainable production model.